Creating Statistics Exercises on the Basis of Research Articles. (July 2019) - Bebermeier, Sarah; Hagemann, Anne
We describe how students can be encouraged to actively review course contents on inferential statistics by creating application-oriented exercises and sample solutions on the basis of concrete and realistic research articles and their data. For evaluation purposes, we use students' reactions to the activity and investigate its effects on the final statistics exam. Students' ratings of the quality of the exercises, necessary knowledge, and the evaluation of the activity were very positive, and participating students achieved better grades in the final exam than nonparticipants, whereas the groups did not differ regarding their initial skills or motivational characteristics. We conclude by discussing implications for lecturers teaching statistics.